Expert System to Determine Camera Price Using VIKOR Method - Hendri Purwanto; Indah Susilawati (International Journal of Informatics Engineering and Computing, 2024)
This study presents the design and implementation of an expert system for determining the best camera recommendations for beginners, utilizing a web-based platform to deliver tailored results based on user input. The VIKOR method is employed to evaluate and rank camera products, ensuring optimal recommendations by balancing multiple criteria such as technical specifications, usability, and cost-effectiveness. Analysis of five camera products revealed that the Fujifilm X-A5 achieved the lowest VIKOR value of 0, indicating it as the top recommendation for beginners. The system's calculations were validated against manual computations, achieving a 100% accuracy rate, and thereby confirming the reliability of the expert system. The proposed system not only enhances decision-making efficiency but also significantly reduces the time required for experts to rank and evaluate multiple camera products. This approach demonstrates the potential of integrating multi-criteria decision-making methods into expert systems to provide accurate, user-centric recommendations in real time.